Collected papers on Greek tragedy - Willink, C. W. (Classical Studies E-Books Online, Collection 2010, ISBN: 9789004222816., 2010)
Sir Charles Willink was responsible for some of the most important advances in the study of the text and metre of Greek tragedy published in the last fifty years. With his unrivalled knowledge of tragic usage and ear for subtle rhythmical points, he was able to solve long-standing problems in areas ranging from metrical analysis to staging and the detection of interpolations, and many of his proposals have already been adopted in standard editions. This volume collects all Willink's published papers, except the two earliest, which are summarized. Three important new articles, on Euripides' Helen , Medea , and Alcestis , are published for the first time, and additions and corrections to the published papers are included, together with an index of passages discussed.